1996
DOI: 10.1063/1.361125
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic properties of γ-Fe2O3 nanoparticles obtained by vaporization condensation in a solar furnace

Abstract: The magnetic properties of γ-Fe2O3 nanoparticles synthesized by vaporization condensation in a solar image furnace have been studied using both magnetic measurements and Mössbauer spectroscopy. The mean size of the particles turns out to be easily controlled by changing the pressure conditions in the growth chamber. The particles exhibit superparamagnetic behavior at room temperature. Magnetic measurements show the appearance of magnetic hysteresis in the low-temperature range and from the evolution with tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
79
1
4

Year Published

1999
1999
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 150 publications
(95 citation statements)
references
References 27 publications
11
79
1
4
Order By: Relevance
“…First, our simple synthetic procedure has resulted in pure nanoscale mesoporous particles of g-Fe 2 O 3 , while most of the literature-reported work involved stabilizing the particles by dispersion into organic or inorganic matrices, [22±30] or by coating with relatively thick layer of organic additives. [31,32,49] Second, all studies that have been reported on the synthesis of pure g-Fe 2 O 3 involved extra steps such as the preparation of a-Fe 2 O 3 first followed by vaporization condensation to convert it to the g-phase, [38] or the preparation of Fe 3 O 4 first followed by oxidation to gFe 2 O 3 . [8,13] Direct precipitation in aqueous media under specific conditions has also resulted in g-Fe 2 O 3 , but this method is very sensitive to experimental conditions especially the pH of the solution which makes the formation of impurities very likely to occur.…”
Section: Resultsmentioning
confidence: 99%
“…First, our simple synthetic procedure has resulted in pure nanoscale mesoporous particles of g-Fe 2 O 3 , while most of the literature-reported work involved stabilizing the particles by dispersion into organic or inorganic matrices, [22±30] or by coating with relatively thick layer of organic additives. [31,32,49] Second, all studies that have been reported on the synthesis of pure g-Fe 2 O 3 involved extra steps such as the preparation of a-Fe 2 O 3 first followed by vaporization condensation to convert it to the g-phase, [38] or the preparation of Fe 3 O 4 first followed by oxidation to gFe 2 O 3 . [8,13] Direct precipitation in aqueous media under specific conditions has also resulted in g-Fe 2 O 3 , but this method is very sensitive to experimental conditions especially the pH of the solution which makes the formation of impurities very likely to occur.…”
Section: Resultsmentioning
confidence: 99%
“…In the bulk, M S (T ) is described by the Bloch T 3/2 law, M S (T ) = M 0 (1 − BT α ) where α is equal to 3/2 and B is the Bloch constant (∝ 1/J). For the un-doped particles, M S (T ) was well represented by the normal Bloch law (α = 3/2), and provided B = 3.83(3)×10 −5 K −3/2 , consistent with an Fe-oxide nanoparticle 40,41 . Modifications to the Bloch law are obtained when a gap in the spin wave spectrum results from a high crystalline anisotropy 42 , or due to finitesize effects 43,44 .…”
Section: Magnetometry (Statics)mentioning
confidence: 92%
“…31,32 In practice, we have found that the value of b for iron oxide, 2.8ϫ 10 −5 K −3/2 , is accurate and that a can vary slightly between samples when the frequency is higher than the blocking frequency but is generally approximately 1.65 for the commercial iron oxide nanoparticles we used, Feridex ® ͑Bayer AG, Leverkusen, Germany͒. These values were used for all the results presented.…”
Section: Iib Factors Complicating the Simple Superparamagnetic Modelmentioning
confidence: 99%
“…31,32 The magnetization follows a Bloch's law T 3/2 relationship impacted by several factors including the coating of the nanoparticles, the surface structure, and the chemical composition. 33 The general relationship is of the form…”
Section: Iib Factors Complicating the Simple Superparamagnetic Modelmentioning
confidence: 99%
See 1 more Smart Citation